The strategy of Spanish NGOs. analysis its determinants (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In the literature, non-profit’s strategies have not been considered in depth. Thereason underneath is related to the thought that non profits do not have any strategyat all. However, strategies could be deliberate and emergent and, then, not explicitly formulated. In this paper, we try to evaluate the factors that affect non-profit strategies–deliberate or emergent- for a sample of non-governmental organizations fordevelopment aid. We analyse the relation between the main external factor of theenvironment (institutional and sector variables) and strategy (Herfindahl index andspecialization ratio). Results show that there exist a strategic logic in the way thoseorganizations choose countries and activities in which to operate.
Keywords: Strategy; non-governmental organizations for development aid; institutional endowment; industry.